Correction: Characterisation of Mesothelioma-Initiating Cells and Their Susceptibility to Anti-Cancer Agents. - Elham Alizadeh Pasdar; Michael Smits; Michael Stapelberg; Martina Bajzikova; Marina Stantic; Jacob Goodwin; Bing Yan; Jan Stursa; Jaromira Kovarova; Karishma Sachaphibulkij; Ayenachew Bezawork-Geleta; Margaryta Sobol; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0119549.].